2020
DOI: 10.1038/s41598-020-69759-5
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Aedes aegypti in urban environments mediated by the availability of key aquatic habitats

Abstract: Aedes aegypti is the main vector of dengue, Zika, chikungunya, and yellow fever viruses. Controlling populations of vector mosquito species in urban environments is a major challenge and being able to determine what aquatic habitats should be prioritized for controlling Ae. aegypti populations is key to the development of more effective mosquito control strategies. Therefore, our objective was to leverage on the Miami-Dade County, Florida immature mosquito surveillance system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 77 publications
(69 reference statements)
1
40
0
Order By: Relevance
“…albopictus , typically regarded to be a peri-urban vector of dengue, has expanded its range to built-up areas of Jaffna city. Urban farms have been reported to provide favourable environments for Aedes mosquitoes in Florida, USA [ 31 , 32 ], and this also appears to be the case in the Jaffna peninsula. A previous GIS-based study showed that the built-up areas of Jaffna city have a high local incidence of dengue [ 33 ], which is consistent with the present findings that show high ovitrap indices in the city.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus , typically regarded to be a peri-urban vector of dengue, has expanded its range to built-up areas of Jaffna city. Urban farms have been reported to provide favourable environments for Aedes mosquitoes in Florida, USA [ 31 , 32 ], and this also appears to be the case in the Jaffna peninsula. A previous GIS-based study showed that the built-up areas of Jaffna city have a high local incidence of dengue [ 33 ], which is consistent with the present findings that show high ovitrap indices in the city.…”
Section: Discussionmentioning
confidence: 99%
“…Among these is the subgenus Kerteszia of the genus Anopheles, the subgenus Microculex of the genus Culex, and the species in the genus Wyeomyia [37][38][39]. Therefore, bromeliads are important aquatic habitats for mosquitoes and require monitoring, both in urban and rural environments [40].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in Miami-Dade County have revealed Ae. aegypti successfully propagates within tank-type bromeliads and are the dominant species found in ornamental bromeliads in urban environments (Wilke et al 2018, Wilke et al 2019, Wilke et al 2020. In order to assess the relationship between disease vector mosquito species and bromeliads in Collier County, Florida, the Collier Mosquito Control District began a district-wide survey of mosquito species found in bromeliads within urban residential and commercial settings, as well as high-traffic tourist destinations.…”
Section: Introductionmentioning
confidence: 99%